EFEKTIVITAS LAYANAN ADMINISTRASI KEPENDUDUKAN BERBASIS ONLINE MELALUI APLIKASI KIOS e-PAKLADI - Ghania Nasha; Isnaini Rodiyah (Journal Publicuho, 2025)
This research commences by pinpointing challenges concerning the efficiency of public services at the community level. It proceeds with gathering data via interviews, observations, and reviewing documents, which is then analysed through the interactive framework developed by Miles and Huberman. This study aims to assess the efficacy of the Kios e-PAKLADI initiative in enhancing both the efficiency and accessibility of administrative services related to the populace in Plintahan Village, located in Pandaan District of Pasuruan Regency. The theoretical basis for this research utilises the notion of public service effectiveness, employing indicators such as accuracy of targets, efficiency of execution, punctuality, and accomplishment of goals. The results show that the initiative has met its objectives, as active citizens are now able to manage administrative paperwork without having to go to the sub-district office. Nonetheless, challenges to technical efficiency persist due to connectivity issues and incomplete document submissions. Additionally, the dissemination of information is not fully effective since village officials primarily receive it rather than the broader community. Achievement of goals can be seen in the rise in service offerings, especially concerning the distribution of Family Cards and ID Cards, while oversight is effectively conducted through digital communication between village officials and the Department of Population and Civil Registration. In summary, Kios e-PAKLADI has a favourable impact on enhancing the efficiency of public services; however, it requires better outreach efforts, improved human resources, and enhanced network infrastructure for the sustainable implementation of digital services.